Urban economics - Mills, Edwin S. (HarperCollins series in economics, 1993)
Urban Economics uses economic theory to analyze cities as well as urban issues and problems. The authors discuss the economic history of U.S. urbanization and regional shifts, and then go on to examine basic theoretical models, including the open-city model, against real-world urban environments. The text concludes by critically evaluating urban problems and the public sector, including discussions of the housing market, transportation, local government, pollution and environmental quality, and urbanization in developing countries. The Fifth Edition includes more coverage on education and an entirely new chapter on housing financiers.